2017
DOI: 10.1158/1538-7445.sabcs16-p1-02-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-02-06: Serial monitoring of circulating tumor DNA in patients with metastatic breast cancer

Abstract: Background: For patients with MBC, there is currently no evidence that changing therapy on the basis of biomarker results improves outcome. Clinical benefit of treatment is defined as complete response, objective response, or stable disease as determined by RECIST criteria on radiological evaluation. Serial measurements of serum biomarkers such as CA2729 and CTCs have proven unsuccessful in predicting clinical benefit. Circulating tumor DNA(ctDNA) has emerged as a potential biomarker that may predict response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Regular ctDNA monitoring can also detect molecular relapse 8–11 months before clinical or radiological relapse is detectable 73 . In the metastatic setting, ctDNA has been shown to be more sensitive than CTC analysis to detect early progression and shows concordance with protein biomarkers such as CA27.29 77 , 78 . Results from metastatic breast cancer have found that ctDNA detection of variants of ESR1 , TP53 , and PIK3CA were predictive of poor overall survival, and may help to identify which patients may benefit from certain treatments 79 .…”
Section: Dicussionmentioning
confidence: 97%
“…Regular ctDNA monitoring can also detect molecular relapse 8–11 months before clinical or radiological relapse is detectable 73 . In the metastatic setting, ctDNA has been shown to be more sensitive than CTC analysis to detect early progression and shows concordance with protein biomarkers such as CA27.29 77 , 78 . Results from metastatic breast cancer have found that ctDNA detection of variants of ESR1 , TP53 , and PIK3CA were predictive of poor overall survival, and may help to identify which patients may benefit from certain treatments 79 .…”
Section: Dicussionmentioning
confidence: 97%